Colonialism and the call to Jihad in British India - Hasan, Tariq (Journalist) (SAGE Publications India, 2015)
"Over a period of time, the role of Muslim religious leaders in the Indian independence movement has been forgotten; and this work is a timely reminder. The book focuses on the current debate around different interpretations of Jihad. It debunks extremists' interpretation of Jihad, and recalls how Indian Muslim clerics in fact used this idea to fight and, in some cases, lead the freedom struggle against the British"--Provided by publisher